Risk-rated economic values for production and functional traits of Small East African goat using profit functions - Mbuku, S.M.; Kosgey, I.S.; Okeyo Mwai, Ally; Kahi, A.K. (American Society of Animal Science, 2014)
The study reports the effect of incorporating risk in the derivation of economic values for traits of the breeding goal of Small East African goats under the pastoral production system. A model previously used to derive conventional economic values was revised to incorporate variances of profit and risk attitudes of livestock keepers in estimation of risk-rated economic values. This resulted in a decrease in the estimated economic values by -14.7% (milk yield), -2.7% (12-month live weight), -23.9% (consumable meat percentage), -6.6% (mature doe live weight), -98% (mature buck live weight), -8.6% (kidding frequency), -8.2% (pre-weaning survival rate), -8.9% (post-weaning survival rate), -8.1% (doe survival rate) and 0% (residual feed intake). The decrease in the conomic values implied that livestock keepers who were risk averse were willing to accept lower expected returns to void the opportunity of unfavourable outcomes.